(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
As a matter of fact, pragmatics which is an important linguistic field plays a vital role in communication and interpretation of the speaker’s utterance leading to positive or negative results. Pragmatics has witnessed many theoretical principles and development since it was founded in the last century. It works side by side with the other different fields like sociology, politics, religion. etc., to give a clear and integrated interpretation of what is said in the communication process. This paper aims at analyzing the American president Trump’s calling "Coronavirus China Virus" and why he said that, but he was criticized by many characters and this led him to defend himself in many occasions. Trump’s calling "Coronavirus China Virus" for racial, political ethno- genic, economic and ideological reasons and to be away from any blaming and responsibility. Finally, he defended himself why he said that "Coronavirus China Virus" using so many hedge ways.